Enabling Mining Activities for Sustainable Development Through Local Content and Corporate Social Responsibilities in Cameroon - Ekabe Elema Joyce (Zien Journals, 2021)
This article deals with enabling sustainability in the mining communities through the concepts of corporate social Responsibility (CSR) and local content in Cameroon. It analyses the concepts of Corporate Social Responsibility and Local content within the domain of mining in Cameroon. In this regard it looks at some of the impacts of Corporate Social Responsibility and Local content on mining communities and their contribution to sustainable development. The methodology used is essentiality qualitative using both primary and secondary sources of information. This paper demonstrates the importance of CSR and Local Content within the mining sector
Keywords: Corporate Social Responsibility; Local Content and Mining Activities